Monetary Compensation and Nontaxable Employee Benefits: An Analytical Perspective - Halperin, Robert; Tzur, Joseph (The Accounting Review, 1985)
[This paper analyzes the payment of monetary compensation (salary) and nontaxable benefits and develops an expansion path for the optimal combination of salary and benefits. The results explain why 1) the employer has an incentive to pay nontaxable benefits instead of salary, 2) benefits such as health insurance are given to lowly as well as highly paid employees while perquisites become a more favored form of compensation as employees' incomes increase, 3) an employee at or near the minimum wage for his or her occupation may receive increases in compensation in the form of increased nontaxable benefits, 4) a broad class of middle management employees are all paid the maximum legal benefits for their job classification, and 5) the employer may authorize the payment of possibly nondeductible benefits to highly compensated executives.]